(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article under consideration analyzes the pecularities of functioning and declination of nominal adjectives of Church Slavonic language of the end of the XVI – XVII centuries. A conclusion about influence of Ukrainian language on these points was made.